Solar photocatalytic degradation of basic red 51 in hair dye bathroom greywater using zinc oxide nanoparticles synthesized with Corriandrum sativum leaf extract - Gopalakrishnan, Yashni (2021)
The high tendency of chemically synthesized ZnO NPs to aggregate causes drop in the solar photocatalytic degradation (SPD). The present study is aimed to formulate ZnO NPs synthesized using Corriandrum sativum leaf extract as a capping agent to prevent aggregation of ZnO NPs for hair dye bathroom greywater degradation (HDBGW). The ZnO NPs were prepared at 100°C [[ZnO [A]] and calcined at 550°C [[ZnO [B]]. The produced ZnO NPs were characterized by field emission scanning electron microscopy with energy dispersive X-ray spectroscopy (FESEM-EDX), transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis/ differential scanning calorimetry (TGA/DSC) and Raman spectroscopy. The SPD of artificial hair dye bathroom greywater (AHDBGW) was optimized based on ZnO loadings, pH and initial Basic Red 51(BR51) concentrations while the kinetic model was investigated using Langmuir-Hinshelwood in an aqueous solution of BR51. The SPD of BR51 degradation pathway was studied using gas chromatography-mass spectrometry (GC-MS). The XRD analysis confirmed the hexagonal wurtzite structure of both types ZnO NPs. The TEM analysis of ZnO NPs [A] and ZnO NPs [B] were between 117 and 149 nm and 71.1 and 102 nm, respectively. FTIR revealed the presence of –C–O, =C-H, C=C, –C–O–C and O–H bonds in both types of ZnO NPs. The best operating parameters for SPD of BR51 in AHDBGW was 0.10 g of ZnO NPs, at pH 5 and with 1 ppm of BR51. It can be observed that SPD of AHDBGW and RHDBGW by ZnO NPs reduces COD and BOD5 concentrations by 80.92% and 79.14% (COD) and 82.91% and 70.18% (BOD5) respectively. The SPD BR51 in aqueous solution follows pseudo first-order kinetics with average rate constants of 0.019, 0.014, 0.008 and 0.005 min-1 for 5, 10, 15 and 20 ppm of BR51 at optimum condition respectively. The SPD pathway determines hexadecanoic acid, methyl ester and octadecanoic acid and methyl ester as safer final products. Hence, it is found that the study represents an effective solution for HDBGW treatment to ensure the environmental sanitation for future generations.